THE MODIFIED HOMOTOPY PERTURBATION METHOD FOR SOLVING FUZZY NONLINEAR DIFFERENTIAL EQUATIONS - A. Jasim, Jinan (MAGISTRA, 2016)
In this paper we recommend a logical algorithm to solve the fuzzy nonlinear differentialequations. The solution by using the fuzzy methods is complicated therefore we will use the cut that relatethe fuzzy equations with the real equations and to facility the steps of solution.This algorithm is formed by the homotopy perturbation method (HPM), Laplace transforms and PadÃ©approximation.We use the modified homotopy perturbation method for reaching to the proper result then we will comparethe result with the original values of .Keyword: Fuzzy, homotopy, algorithm